QSAR study of antimycobacterial activity of quaternary ammonium salts of piperidinylethyl esters of alkoxysubstituted phenylcarbamic acids - Waisser, K; Dolezal, R; Palát, K; Cizmárik, J; Kaustová, J (Folia microbiologica, 2006)
A series of 17 halogenides of quaternary ammonium salts of the alkylpiperidinylethyl esters of 2-pentoxy (and 2-heptoxy) substituted phenylcarbamic acids were evaluated for in vitro antimycobacterial activity against Mycobacterium tuberculosis, M. kansasii, and M. avium. Correlation of this action with lipophilicity (log P, 1-octanol-water system) was used for the description of the structure-antimycobacterial activity relationships (QSARs). The activity increased with the increasing lipophilicity of the compounds.
Keywords: Antitubercular Agents; molekulární struktura; kvartérní amoniové sloučeniny; antibakteriální látky; Molecular Structure; Mycobacterium kansasii; Microbial Sensitivity Tests; Phenylcarbamates; fenylkarbamáty; kvantitativní vztahy mezi strukturou a aktivitou; Quantitative Structure-Activity Relationship; Quaternary Ammonium Compounds; Anti-Bacterial Agents; antituberkulotika; Mycobacterium avium; mikrobiální testy citlivosti; Mycobacterium tuberculosis